2016
DOI: 10.1103/physrevb.93.205405
|View full text |Cite
|
Sign up to set email alerts
|

Quantum hydrodynamic theory for plasmonics: Impact of the electron density tail

Abstract: Multiscale plasmonic systems (e.g. extended metallic nanostructures with sub-nanometer interdistances) play a key role in the development of next-generation nano-photonic devices. An accurate modeling of the optical interactions in these systems requires an accurate description of both quantum effects and far-field properties. Classical electromagnetism can only describe the latter, while Time-Dependent Density Functional Theory (TD-DFT) can provide a full first-principles quantum treatment. However, TD-DFT be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
199
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(201 citation statements)
references
References 113 publications
1
199
1
Order By: Relevance
“…The functional derivative of the leading term of the density gradient correction gives the Bohm potential of quantum hydrodynamics: VB=28me0.25emδδn()trueγD(),nTn()r2n()rdboldr=prefix−228meγD(),nT2nn+scriptO()()n1true/n02. …”
Section: Relation Between the Polarization Function In The Rpa And Thsupporting
confidence: 92%
See 1 more Smart Citation
“…The functional derivative of the leading term of the density gradient correction gives the Bohm potential of quantum hydrodynamics: VB=28me0.25emδδn()trueγD(),nTn()r2n()rdboldr=prefix−228meγD(),nT2nn+scriptO()()n1true/n02. …”
Section: Relation Between the Polarization Function In The Rpa And Thsupporting
confidence: 92%
“…The functional derivative of the leading term of the density gradient correction gives the Bohm potential of quantum hydrodynamics [27][28][29] :…”
Section: Relation Between the Polarization Function In The Rpa And Thmentioning
confidence: 99%
“…In this respect, it was shown that the nonlocal correction and the spill‐out effects have counteracting influences (Figure d) . In the treatment of the spill‐out effects careful consideration should be given to the calculation of the spatial dependence of the equilibrium electron density, to which the results are very sensitive …”
Section: Free‐electron Dynamics In Plasmonic Nanostructuresmentioning
confidence: 99%
“…[39,40] In the treatment of the spill-out effects careful consideration should be given to the calculation of the spatial dependence of the equilibrium electron density, to which the results are very sensitive. [41] Other examples of linear nonlocal hydrodynamic effects include the modification of the molecular fluorescence [42] as well as the plasmonic field confinement and enhancement [43][44][45][46] , the latter effects lead to the re-evaluation of SERS efficiency [47] and are also important in the context of nonlinear optics. For a recent review on the linear nonlocal hydrodynamic phenomena we refer the reader to Ref.…”
Section: Linear Free-electron Dynamicsmentioning
confidence: 99%
“…But when the sizes approach the nanoscale, the model is no longer able to explain experimentally observable phenomena like, for example, the blueshift of the resonance frequency of the localized surface plasmon (LSP) in metallic nanospheres [1]. An improved model that has been successful in describing the optical properties of metals on the nanoscale is the hydrodynamic Drude model (HDM) [2][3][4][5][6][7][8][9][10][11][12]. In this model, the polarization depends nonlocally on the electrical field, and the aforementioned blueshift appears as a size-dependent nonlocal effect [7,13,14].…”
Section: Introductionmentioning
confidence: 99%